Citotaxonomia dos triatomíneos: a citogenética como ferramenta no estudo do complexo Triatoma brasiliensis e do subcomplexo Brasiliensis - Alevi, Kaio Cesar Chaboli [UNESP] (2014)
Cytogenetic analyzes have shown to be important tools to study the taxonomy of the triatomines. Thus, the use of cytogenetic techniques may clarify the problems existing in the current classification of species that form the Brasiliensis subcomplex. The species in the subcomplex were grouped only by morphological data and geographical distribuition and differs from the species in the Triatoma brasiliensis complex, on the basis of on different approaches that indicate the monophyly. The present paper describes cytogenetically T. lenti, T. sherlocki, T. melanocephala and T. vitticeps, in order to evaluate the position of these vectors in the Brasiliensis subcomplex and analyze a possible relationship of T. lenti, T. melanocephala and T. vitticeps with the T. brasiliensis complex. Classical cytogenetic analysis (Lacto-acetic orcein, silver nitrate staining and C banding) and molecular (in situ hybridization - FISH) were performed in adult males. T. lenti and T. sherlocki showed several chromosomal characteristics in common, such as the number of chromosomes (2n = 20A + XY), disposition of constitutive heterochromatin in the autosomes (one or both ends of the autosomes) and the staining of nucleolar organizer regions (NORs) (a pair of autosomes). These insects were able to be differentiated by markings observed in spermatids, which were proposed as a diagnostic tool cytotaxonomic. T. melanocephala and T. vitticeps shared the chromosome number (2n = 20A + X1X2X3Y) and the same characteristics during spermatogenesis. However, these vectors were able to be differentiated by the disposition of heterochromatic blocks, by the arrangement of NORs and the examination of spermiogenesis. Thus, these characteristics corroborate the position of T. lenti and T. sherlocki on Brasiliensis subcomplex and and we propose the exclusion of T. melanocephala, T. vitticeps and T. tibiamaculata because they present fragmentation of the sex chromosome X and are ...